The adaptation of scientific reasoning of prospective teachers for primary education in the perspective of civic science - Hidayah, Yayuk; Dewi, Dinie Anggraeni; Trihastuti, Meiwatizal (Jurnal Civics: Media Kajian Kewarganegaraan, 2021)
This article aims to determine the adaptation of prospective elementary school teachers' scientific reasoning from a civic science perspective through seminar courses on elementary schools' educational problems. The issue of distance learning during the Corona Virus Disease (Covid) 19 pandemic in Indonesia has led to various highlights and analyzes. The learning scheme's quality and learning scheme are among the most popular questions in this learning scheme. This research uses a case study with a qualitative approach with data collection using interviews, observation, documentation, and literature studies. The results showed that the adaptation of the scientific reasoning of prospective elementary school teachers in a civic science perspective through the Seminar on Educational Problems in Primary Schools has several characteristics,  that is: 1) educational problems in primary schools captured by dominant students in technological literacy, 2) study of educational problems in schools fundamental relates to the realization of smart and good citizens that reflected in attitudes and behavior in the Covid-19 pandemic situation, and 3) there is character building in the adaptation of scientific reasoning in the civic science perspective. Therefore, the research expects to have implications in developing civic education knowledge, especially in elementary school, which aims to strengthen the study of civic education.